Steve & Me - Irwin, Terri (London Simon & Schuster, 2007)
From the woman who knew Steve Irwin best comes a loving, moving story of their life together, his astonishing legacy, and the man behind the Crocodile Hunter phenomenon. 16-page full-color photo insert
Include Color Illustration
Keywords: Irwin, Steve, 1962-2006 -- Australia -- Herpetologists